2017
DOI: 10.1371/journal.pone.0172554
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology of Mycobacterium tuberculosis complex in Brussels, 2010–2013

Abstract: The tuberculosis (TB) incidence rate in Brussels-Capital Region is 3-fold higher than in Belgium as a whole. Eight years after the realization of initial prospective population-based molecular epidemiology investigations in this Region, a similar study over the period 2010–2013 was conducted. TB strains isolated from 945 patients were submitted to genotyping by standardized 24-locus-MIRU-VNTR typing and spoligotyping. The phylogenetic analysis showed that the LAM (16.7%) and Haarlem (15.7%) branches are the tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 24 publications
1
21
0
1
Order By: Relevance
“…It was also noticed that in almost every cluster, there were isolates with the 12 nucleotide insertion in the rpo B gene. The presence of clusters with identical genotypes among the isolates is an indicator of the transmission of the same strain [ 51 ]. In this study, no correlation about the clusters and patient's information was found to determine any kind of transmission, probably due to low clustering rate of the isolates.…”
Section: Discussionmentioning
confidence: 99%
“…It was also noticed that in almost every cluster, there were isolates with the 12 nucleotide insertion in the rpo B gene. The presence of clusters with identical genotypes among the isolates is an indicator of the transmission of the same strain [ 51 ]. In this study, no correlation about the clusters and patient's information was found to determine any kind of transmission, probably due to low clustering rate of the isolates.…”
Section: Discussionmentioning
confidence: 99%
“…However, we observed that individuals below the age of 30 years were associated with recent TB transmission, and this is similar to observations made elsewhere. 28,30 Also from this study, we observed that each year increase in age is associated with an approximately 1% (CI: 0·13 − 2·00, p=0·007) decrease in the odds of a TB patient being part of a recent transmission event implying that, compared to younger individuals, older individuals are more likely to get active TB disease by reactivation of latent TB infection rather than through a recent transmission event. 28 This finding put age as a risk factor for recent TB transmission in Ghana.…”
Section: Discussionmentioning
confidence: 53%
“…The first VNTRs described in mycobacteria were those identified in M. tuberculosis , collectively referred to as mycobacterial interspersed repetitive units (MIRUs) 37 . Although the panel of MIRU-VNTR loci has been modified over the years, the standardized 24-locus MIRU-VNTR typing is currently recognized as the reference typing system for M. tuberculosis complex 38 40 . The principle of the VNTR-based typing modalities involves PCR amplification of a predefined set of VNTR loci, by using primers annealing to their flanking sequences, and amplicon size determination to deduce the number of TR units within each locus.…”
Section: Discussionmentioning
confidence: 99%